2018
DOI: 10.33545/gynae.2018.v2.i2b.57
|View full text |Cite
|
Sign up to set email alerts
|

A Kap study on menstrual hygiene in adolescent girls

Abstract: Objective of Study: To study Awareness and hygienic practice among adolescent girls during menstruation. Aims and Objectives: To study demographic profile of study group and to assess hygiene practices during menstruation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Young people are more likely to adopt unhealthy behaviors and encounter many problems related to their sexual and reproductive health [8]. Because of this transition, young girls face difficulties in managing their menstruation and are exposed to societal taboos [9] However, menstruation or menses is a normal process in females when they reach reproductive age [10].There is evidence that, both in developed and underdeveloped countries, girls experience the early onset of menstruation due to changes in lifestyle, environmental factors, and geographical location [11]. A study in Pakistan reported an age of 12 to 14 years for menarche [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young people are more likely to adopt unhealthy behaviors and encounter many problems related to their sexual and reproductive health [8]. Because of this transition, young girls face difficulties in managing their menstruation and are exposed to societal taboos [9] However, menstruation or menses is a normal process in females when they reach reproductive age [10].There is evidence that, both in developed and underdeveloped countries, girls experience the early onset of menstruation due to changes in lifestyle, environmental factors, and geographical location [11]. A study in Pakistan reported an age of 12 to 14 years for menarche [11].…”
Section: Introductionmentioning
confidence: 99%
“…Girls in developing countries encounter problems in managing menstruation properly because they lack the basic facilities of WASH (water, sanitation, and hygiene), proper information, a suitable environment, and support, which ultimately, affects their basic human rights to education, health, and privacy [16,17]. This is due to a lack of knowledge, improper awareness, and poor attitudes and practices towards menstruation and menstrual hygiene [5,9]. Additionally, several studies have revealed that the lack of availability of WASH facilities at schools, anxiety about blood dripping onto clothes, a lack of access to sanitary pads, and the poor attitudes of male students and teachers towards menstruation are linked with poor menstrual hygiene [18].…”
Section: Introductionmentioning
confidence: 99%